Kyrkorna i Klåstad: En presentation av ett pågående projekt - Hedvall, Rikard (Hikuin, 2003)
The churches in Klåstad. A presentation of a progressive projekt By Rikard Hedvall In 1997 an unknowed round naved churchruin was discovered in Klosterstad/Klåstad, Östergötland. The church dates approximately to the first half of the 13th century. It was destroyed in a fire between 1561 and 1567. A lot of the medieval interior was still extant. An earlier stavchurch was discovered a few meters north of the round naved church. This church dates from the 11th century and have been replaced when the round naved church was completed. Even the belltowers to both churches have been excavated. Totaly 30 pieces of limestone gravemonuments, from the same location, decorated with dragonmotives and runic inscription have been found. This type of monuments dates approximately from the 11th century to the beginning of the 12th century. Among almost 200 excavated graves one of them which belong to that early church was covered with a runic inscripted monument.